Self-compassion enhances ıntuitive eating patterns in middle-aged adults - Krista Irmischer; Marina I. Cans; Jolanta Burke; Annette Sweeney (Journal of Happiness and Health, 2024)
Over time, humans have experienced varied and shifting relationships with food in both negative and positive ways. Mostly negative results have emerged from restrictive diets, while approaches to food that include more self-trust indicated healthier impacts. The current study focused on the positive approach to eating and addressed a relationship between intuitive eating and dimensions of self-compassion and wellbeing.  Data were collected using an online survey, which assessed demographics, BMI, self-compassion, intuitive eating, and wellbeing. A cohort of 234 participants, comprising both men and women, predominantly women aged 36-65, responded to the survey. Within this group, a subset of 148 participants provided supplementary information regarding their weight and height. Regression analysis showed that after controlling for wellbeing, 24% of the variance in intuitive eating was explained by self-compassion. Specifically, the self-compassion components that best predicted intuitive eating were reduced self-judgement and increased common humanity. No correlation was observed between self-compassion and BMI, age and gender. Contrary to previous research, a positive correlation between BMI and intuitive eating was observed. Further research is needed to study the relationship among IE, BMI, and dietary quality, along with investigating the connection between IE and varying physiological responses according to BMI status, age and gender. The results are discussed in the context of policy and practice.